Strategi Lembaga Amil Zakat Infak Shadaqah Muhammadiyah Kabupaten Tulungagung Dalam Meningkatkan Kepercayaan Muzakki - Eva Fahmadia Jilan Maulida; Ahmad Muhtadi Anshor (ZAWA: Management of Zakat and Waqf Journal, 2022)
Zakat is the leading financial instrument among Muslims. Therefore, muzakki's trust in the Amil Zakat Institution must be encouraged to increase groups. Furthermore, this study aims to determine the LAZISMU strategy in Tulungagung Regency to increase muzakki confidence and determine the supporting and obstacles factors in increasing muzakki trust. This study used field research with a qualitative approach descriptively to get the information concerning an existing condition. As a zakat management institution, LAZISMU Tulungagung Regency uses various strategies to increase the trust of muzakki, including Distribution of trustworthy zakat infaq and shadaqah funds, transparency of fund management, improving service quality, and maintaining relationships with muzakki. This strategy aims to increase muzakki trust carried out by LAZISMU Tulungagung Regency. In addition, in 2021, around 90% of the Tulungagung Regency Muhammadiyah Association members will receive ZIS funds through LAZISMU Tulungagung Regency.